Pengaruh Kedisiplinan Keaktifan Belajar Kelompok Dengan Prestasi Belajar Siswa SMK Kehutanan Wali Sembilan Tuban - Ahmad Kholil; Muhtadi; Atim S (FAI- Undar, 2019)
The topic of discussion of this thesis is the influence of group learning activity discipline on student achievement at the forestry vocational school guardian nine tuban; The writing of this thesis is based on the problem and assumption that learning achievement is the dream of every party involved in the world of education, be it teachers, parents or students concerned, and to achieve good learning achievement, it is necessary to grow students' willingness to learn, among others by through group learning activities. While the problems raised in writing this thesis are: is there any influence of group learning activity discipline on student learning achievement of wali nine forestry vocational high school students, so that the purpose of the discussion of this thesis is to find out how far the influence of group learning activity discipline on student learning achievement of guardian nine forestry vocational high school students. From the problems and objectives above, then based on the existing theory, the following hypothesis is formulated: the influence of group learning activity discipline on student achievement of the wali nine forestry vocational high school students. The next step is to solve the problem and test the existing hypotheses, then use the methods, namely the method of determining the population, the method of determining the respondents in a populative manner, while the data collection used is the observation method, the questionnaire method, the interview method and the documentary method. And after all the data has been collected, it is analyzed using the X2 (Chi Square) formula followed by the KK (Contingency Coefficient) formula to find out the extent of the influence of the relationship discipline. And after being analyzed, then interpreted by producing a conclusion that there is a relationship between the influence of group learning activity discipline and student achievement at the Wali Nine Forestry Vocational High School with a moderate relationship category.